Metaphor as pedagogy in teacher education. (August 2017) - Lynch, Heather L.; Fisher-Ari, Teresa R.
Abstract: Two teacher educators used metaphors to create spaces for students to express their shifting understandings of curriculum over time. This paper centers upon their reflection and analysis of affordances and limitations of metaphor as a pedagogical strategy for supporting students. Instructors noted a) critical shifts in students' dispositions and understanding over time, b) meaningful insights into students' needs for addition support, c) how powerfully relationships were nurtured with students, d) and the quilted nature of the metaphors created, both across students and over time. Limitations are noted, as well as directions for future research. Highlights: Metaphors illuminated students' shifts in understandings of curriculum. Metaphors informed instructors when students needed additional support. Metaphors allowed instructors to build relationships and honor holistic learning. Metaphors were individual, idiosyncratic, relevant, and supportive for students. The metaphors led to "quilted understandings" of curriculum.